Paul and John the Baptist: An Odd Couple? - Michaels, J. Ramsey (1991)
An exploration of possible connections between John the Baptist and Paul, with particular reference to the portrait of Paul in Acts.
Keywords: Acts; Epistles; john the baptist; paul; New Testament